- Desain Pembelajaran Materi Sistem Pertidaksamaan Linear Dua Variabel dengan Model Problem Based Learning (PBL) untuk Siswa SMA: - - Lestari, Nur Puji Lestari (Jurnal Riset Pendidikan Matematika Jakarta, 2025)
This paper presents the development of the learning design for the Two Variable Linear Inequality System (SPLtDV) material using the Problem Based Learning (PBL) learning model for high school students. To find out the suitability of the learning model with the teaching material, student analysis, needs analysis, and task analysis are discussed in detail. PBL stages consist of 5 phases, namely 1) student orientation to problems; 2) organize students to learn; 3) guide individual and group investigations; 4) develop and present the work; and 5) analyze and evaluate the problem solving process. The results and discussion are discussed in detail to determine the suitability of the selection of teaching materials with the chosen learning objectives and how the learning activities support the learning objectives. Then to determine the effectiveness of the PBL design, it is necessary to evaluate both formative evaluation and summative evaluation.